Uji Aktivitas Ekstrak Metanol dan n-Heksan Daun Buas-Buas (Premna serratifolia Linn.) pada Larva Nyamuk Demam Berdarah (Aedes aegypti Linn.) - Ari Hepi Yanti, Mia Aisyiah Lestari, Mukarlina, (Universitas Tanjungpura, 2014)
Dengue fever with A. aegypti as its main vector is a lethal disease. One effort that can be done tocontrol the Dengue fever from spreading is to break the chain of A. aegypti’s life cycle at larvae stage. This study aims to determine the concentration of LC50-24 hours leaves extract of P. serratifoliaand the solvents of P. serratifolia leaves extract that gives best toxicity to inflict death on A. aegypti larvae. The study was conducted during June to September 2013. ANOVA results shows that methanol extract and n-hexane extract of P. serratifolia leaves give significant effect on mortality of A. aegypti larvae. The value of LC50-24 hours methanol extract of P. serratifolia leaves was 2.691,53 ppm whereas that of n-hexane extract was 2.818,38 ppm. Methanol extract of P. serratifolia leaves has more toxicity compared to n-hexane extract.